All is not forgiven - Kenda, Joe (Ashland, Oregon : Blackstone Publishing, 2023)
In this first novel, rookie Detective Joe Kenda, mentored by his veteran partner Detective Lee Wilson, investigates a 1975 case that begins with the murder of a beloved Colorado philanthropist and society figure whose husband, a gambler and womanizer, appears to have an air-tight alibi.
Keywords: Police -- Fiction; Serial murderers -- Fiction; Homicide investigation -- Fiction; Socialites -- Crimes against -- Fiction; Colorado -- Fiction; Detective and mystery fiction; Mystery fiction